2011
DOI: 10.1111/j.1533-2500.2010.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Oxygen‐Ozone Therapy and Combined Use of Oxygen‐Ozone Therapy with Percutaneous Intradiscal Radiofrequency Thermocoagulation for the Treatment of Lumbar Disc Herniation

Abstract: Ozone-PIRFT is more efficacious than ozone alone in reducing pain scores, analgesic consumption, improving functional outcome, and satisfaction of patients with contained lumbar disc herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 21 publications
0
34
0
4
Order By: Relevance
“…Patients who do not respond to conservative therapies, present neurological findings, or have complaints related to compression are candidates for surgery. The rate of recurrence after surgery in these patients is as high as 40% . Therefore, nonsurgical treatments are needed before surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who do not respond to conservative therapies, present neurological findings, or have complaints related to compression are candidates for surgery. The rate of recurrence after surgery in these patients is as high as 40% . Therefore, nonsurgical treatments are needed before surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Both RCTs using OOT showed improvement in pain and disability at 6 months. Gautam et al [23] demonstrated benefit of OOT alone with perhaps a cumulative effect of PIRFT when used as an adjunct. Likewise, Li et al showed additional benefit with psoas compartment block in combination with OOT.…”
Section: Discussionmentioning
confidence: 97%
“…A study by Guatam et al in 2011 aimed to evaluate the efficacy of oxygen-ozone therapy (OOT) alone and when used in conjunction with IDRFT [23]. This study demonstrated promising results for patients with pain secondary to contained lumbar disc herniation.…”
Section: Ablative Proceduresmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, medical ozone treatment of herniated disk exerts analgesic and anti-inflammatory effects. [3] In this paper, we present a case of pneumocephalus in a patient who received medical ozone treatment after failed back surgery and review the related literature.…”
Section: Severe Headache Following Ozone Therapy: Pneumocephalusmentioning
confidence: 99%